Transport Connectivity, Medical Supplies, and People's Health Care Access : Evidence from Madagascar - Iimi, Atsushi; Rajoela, Voahirana Hanitriniala (World Bank, Washington, DC, 2018)
Health care access is a challenge in rural areas in Africa. On the demand side, rural people are often poor, and transport connectivity is typically bad in rural and remote areas. Because of limited transport connectivity, the quality of health care services provided is also often compromised. In Madagascar, the poor condition of the road network has long hampered the sustainability of the medical supply chain in rural areas. The paper shows that people's demand for health care services is affected not only by local transport connectivity, but also availability of medical supplies at the health facility level, which is also determined by primary and secondary road network connectivity. This in turn further suppresses people's demand in rural areas. The results also indicate that it is important to ensure financial affordability among the poor, which is found to be one of the most crucial constraints.